(x+3)*(x+4)*(x+5)=0

Simple and best practice solution for (x+3)*(x+4)*(x+5)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+3)*(x+4)*(x+5)=0 equation:


Simplifying
(x + 3)(x + 4)(x + 5) = 0

Reorder the terms:
(3 + x)(x + 4)(x + 5) = 0

Reorder the terms:
(3 + x)(4 + x)(x + 5) = 0

Reorder the terms:
(3 + x)(4 + x)(5 + x) = 0

Multiply (3 + x) * (4 + x)
(3(4 + x) + x(4 + x))(5 + x) = 0
((4 * 3 + x * 3) + x(4 + x))(5 + x) = 0
((12 + 3x) + x(4 + x))(5 + x) = 0
(12 + 3x + (4 * x + x * x))(5 + x) = 0
(12 + 3x + (4x + x2))(5 + x) = 0

Combine like terms: 3x + 4x = 7x
(12 + 7x + x2)(5 + x) = 0

Multiply (12 + 7x + x2) * (5 + x)
(12(5 + x) + 7x * (5 + x) + x2(5 + x)) = 0
((5 * 12 + x * 12) + 7x * (5 + x) + x2(5 + x)) = 0
((60 + 12x) + 7x * (5 + x) + x2(5 + x)) = 0
(60 + 12x + (5 * 7x + x * 7x) + x2(5 + x)) = 0
(60 + 12x + (35x + 7x2) + x2(5 + x)) = 0
(60 + 12x + 35x + 7x2 + (5 * x2 + x * x2)) = 0
(60 + 12x + 35x + 7x2 + (5x2 + x3)) = 0

Combine like terms: 12x + 35x = 47x
(60 + 47x + 7x2 + 5x2 + x3) = 0

Combine like terms: 7x2 + 5x2 = 12x2
(60 + 47x + 12x2 + x3) = 0

Solving
60 + 47x + 12x2 + x3 = 0

Solving for variable 'x'.

The solution to this equation could not be determined.

See similar equations:

| (x+3)*(x+4)*(x-5)=0 | | 10/7x=-1 | | x+22=134 | | -7x+23=-14x+79 | | (2.5-Z)/(2.5-1)=0.66 | | 4x^2=x^2+135 | | 0.3a^2b-ba^2= | | 3x+05=2x | | 2(x+1)-4(x-1)=10 | | 7x-17=-11 | | 4(5n-7)=10x+2 | | .5=logx | | 9-x=3^1/2 | | 2^x=1/128 | | 1=4tan(2x+1)-1 | | x+1*2x-1= | | 5x+14=14-9x | | 2x+51=3x+54 | | ax=5x+11 | | z+81=97-7 | | 6/7=u/12 | | 2(sin^6x+cos^6x)-3(sin^4x+cos^4x)=-1 | | f(7-x)=3(7-x)+7 | | 6.25=-0.5 | | 4(2x-9)=5(6-x) | | 8x-3(x+4)=3x-26 | | X9=11/5 | | (3t^2+12t-36)=0 | | (9y)-1=y(-25) | | 3x=2-2x | | −2/3×−4/5÷−1/2 | | x^4-27x+100=0 |

Equations solver categories